2016
DOI: 10.1016/j.actamat.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

The role of aluminium in chemical and phase segregation in a TRIP-assisted dual phase steel

Abstract: In this work we demonstrate that micro-segregation patterns of alloying elements present in a high-strength TRIP-assisted DP steel after casting are retained in the microstructure throughout processing, and lead to anisotropy (banding) in the final microstructure. In particular, we have assessed the role of Al on the chemical segregation of Mn, Cr and Si during casting, and their impact on the phase transformations occurring during thermo-mechanical processing of the as-cast material. We have derived the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Further, aluminum acts as strong ferrite-stabilizer element, promoting the austenite to ferrite phase transformation and drastically increasing the local ferrite volume fraction [46]. Thus, the collected data prove the complete irrelevance of austenite content and morphology on the hot-dip aluminizing.…”
Section: Discussionmentioning
confidence: 70%
“…Further, aluminum acts as strong ferrite-stabilizer element, promoting the austenite to ferrite phase transformation and drastically increasing the local ferrite volume fraction [46]. Thus, the collected data prove the complete irrelevance of austenite content and morphology on the hot-dip aluminizing.…”
Section: Discussionmentioning
confidence: 70%
“…In our previous work we demonstrated that micro-segregation patterns of alloying elements present after casting in a high-strength DH steel are retained in the microstructure throughout thermo-mechanical processing, leading to martensite-rich banding in the final microstructure [5]. Aluminium was shown to have a hitherto overlooked role in the segregation of alloying elements during casting, and the single largest influence on the phase transformations occurring during processing that lead to banding in this steel.…”
Section: Introductionmentioning
confidence: 90%
“…The steel under investigation is a high-strength dual phase steel with improved formability, termed DH800, produced via continuous casting followed by hot-rolling (HR), cold-rolling (CR) and continuous annealing. The chemical composition of this steel is given in Table 1, together with the segregation coefficient of the relevant elements [5]. [12,13].…”
Section: Materials Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) in Ref. [1]:Ae3(°C)=c0+X,kcXkXk+X,Y,k,mcXkYmXkYm+X,Y,Z,k,m,ncXkYmZnXkYmZnwhere Ae 3 temperature is expressed in °C and concentrations in wt. %.…”
Section: Datamentioning
confidence: 99%